Exceptional localization of intramuscular hemangioma: Insights from a 66-year-old case - Joud Boutaleb, MD; Basma Beqqali, MD; Sarah Loubaris, MD; Manal El Beyeg, MD; Ouijdane Zamani, MD, PhD; Znati Kaoutar, MD, PhD; Rachida Saouab, MD, PhD; Jamal El Fenni, MD, PhD (Radiology Case Reports)
Intramuscular hemangiomas are rare benign vascular tumors, accounting for less than 1% of all hemangiomas. They often present with subtle symptoms that gradually worsen over time. Magnetic resonance imaging (MRI) is the gold standard for diagnosis, providing detailed lesion characterization. Surgical resection remains the preferred treatment. We report the case of a 66-year-old patient with a painful swelling in the calf that had progressively increased in size over ten years, originating from the flexor hallucis longus muscle.